Investigative Information Management, Learning Organization and Influencer Marketing of Members of the Bor-sae Investigative Organization - Prasert, Seksonna; Kongyoungyune, Pinavet; Fakfuangbun, Thanaorn; Jungtanasombut, Kornkamol; Chan Uam, Anun (Journal of Dhamma for Life, 2025)
The purposes of this study were to : study the relationship between investigative information management, learning organization, and influencer marketing of members of the investigation organization. The population consisted of 2,450 members of the investigation organization who had been trained and implemented the mission of the investigation organization. The sample group was obtained from Crazy and Morgan's table with a .05 error of 335 people. The research instrument used to collect data was a questionnaire with a reliability value of 0.974. This study was a quantitative survey research. The results of the research found that the pairwise relationship between investigative information management, learning organization, and influencer marketing of members of the investigation organization had a statistically significant positive relationship in every pair. The learning organization had a relationship with influencer marketing of 0.784 (p < 0.01). Therefore, it is important to drive and enhance the organization's ability to respond to and utilize the influence of influencers in creating a strong learning organization. Effective data management is an important strategy for developing and maintaining the organization's competitiveness.